Anton Chekhov and Robert Koch Cheek to Cheek: A Proteomic Study. Issue 9 (2nd May 2018) - D'Amato, Alfonsina; Zilberstein, Gleb; Zilberstein, Svetlana; Golovan, Mikhail Ivanovich; Zhuravleva, Anastasiya Anatolyevna; Righetti, Pier Giorgio
Abstract: Five different letters and post cards as well as the shirt worn by Anton Chekhov on his death bed, stored in the State Literary‐Memorial Museum‐Reserve A. P. Chekhov Melikhovo (nearby Moscow), have been analyzed by applying EVA (an ethyl vinyl acetate foil studded with crushed strong anion and cation exchangers and with C8 resins) diskettes to these surfaces. Three different eluates (under acidic and basic conditions and with acetonitrile) were analyzed by high resolution mass spectrometry. The environmental microbiota present on samples and the Mycobacterium tuberculosis strain were described by a meta‐proteomics approach. Eight identified M. tuberculosis proteins confirmed the presence of the bacterium and the cause of Chekhov's death, in addition to several sequenced peptides belonging to other bacterial species. The human plasma proteins and human keratins, detected on a tiny blood spot on the shirt, demonstrated the power of the combined approach.